Words of Wisdom: Ukrainian Proverbs - Hong, Sogu (Archives of Business Research, 2021)
This study aims to analyze Ukrainian proverbs, which are the word of wisdom and living philosophies of Ukrainians. It covers not only functions and styles of Ukrainian proverbs, but also techniques used in them. Since Ukrainian proverbs have a great variety of subjects, this study focuses on 10 main ones, that are recognized as important in Ukrainian life and frequently appear as a topic of proverb: customs and superstitions, history, weather, health, God and priest, truth and justice, the rich and the poor, family relationships, immigrant life, and Ukrainian life in Soviet period. This study introduces the proverbs most frequently recited among Ukrainians with translation and explains their characteristics.